Photoredox-catalyzed C–C bond cleavage of cyclopropanes for the formation of C(sp 3)–heteroatom bonds - Liang Ge; Chi Zhang; Chengkai Pan; Ding-Xing Wang; Dong-Ying Liu; Zhi-Qiang Li; Pingkang Shen; Lifang Tian; Chao Feng (Nature Communications, 2022)
The development of new methodologies for the construction of C(sp 3)–heteroatom bonds under mild conditions is desirable. Here the authors report the formation of C(sp 3)–heteroatom bonds via ring opening of arylcyclopropanes enabled by photoredox catalysis.